THE IMPLEMENTATION OF INTERNET FINANCIAL REPORTING (IFR) IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Zumratul Meini; Khairul Saleh L. Tobing; Dhieka Avrilia Lantana; Kumba Digdowiseiso; Siti Nurain Muhmad (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The implementation of Internet Financial Reporting (IFR) in Indonesia has emerged as a crucial area of emphasis in endeavors to enhance transparency and accountability in corporate financial reporting. It entails the promotion by regulatory and financial authorities to incentivize registered companies to electronically disclose their financial reports. The objective of this study is to enhance accessibility to company financial data, thereby benefiting stakeholders including investors, analysts, and the general public by making it more convenient and expeditious. The employed research methodology is Systematic Literature Review (SLR). The outcome is enhanced transparency and efficiency in the display of financial data, which has the potential to bolster stakeholder confidence. The implementation of IFR has demonstrated the significant advantages it offers in bolstering the expansion of the financial and investment industries in Indonesia. Nevertheless, the absence of International Financial Reporting (IFR) may restrict the availability of financial data, potentially diminishing stakeholder confidence, amplifying ambiguity, and impeding the expansion of the financial industry. Implementing IFR is crucial for fostering economic development and ensuring the integrity of capital markets in Indonesia. Through ongoing progress, it is anticipated that IFR will persist as the primary foundation for upholding transparency and efficiency in corporate financial reporting, rendering it a valuable resource in the rapidly advancing Indonesian economy.